Modeling Study on Oil Particle Filtration Performance of a Composite Coalescing Filter - Lyu, Le; Zhang, Jun; Xu, ChengWei (Frontiers in Energy Research, 2022)
The traditional theoretical model is not suitable for the simulation of the oil particle filtration process of a composite filter due to its huge difference in fiber diameter. In this paper, the concept of fiber dispersion σ was introduced into a mathematical model for describing the dynamic filtration process of a composite filter. The results show that the model is in good agreement with the experimental data. As the packing density is constant, the higher the fiber dispersion, the better performance is. In addition, the effect of different factors on the efficiency of different mechanisms was discussed. For fine particles (<0.1 μm), diffusion is the dominant mechanism. For coarse particles (>1 μm), the inertia impaction mechanism dominates the filtration efficiency. The fiber diameter has a significant effect on the inertia impaction mechanism. The single-fiber efficiency by inertia impaction mechanism is obviously affected by filtration velocity. The packing density has an effect on all mechanisms except for the diffusion mechanism. Moreover, such a model would contribute to an accurate prediction of the dynamic filtration performance of composite filters with polydisperse fiber diameter and improve performance by adjusting parameters reasonably.